Chinchaysuyoa, a new genus of the fish family ariidae (Siluriformes), with a redescription of chinchaysuyoa labiata from ecuador and a new species description from Peru - Marceniuk, Alexandre Pires [UNESP]; Marchena, Jose; Oliveira, Claudio [UNESP]; Betancur, Ricardo R. (Magnolia Press, 2019)
In recent years, morphological and molecular studies have improved our understanding about the relationships and classification schemes of the marine catfishes of the family Ariidae. A taxonomic issue that is still contentious concerns the limits and status of the freshwater Neotropical ariid diversity, in particular the species in the genus Potamarius. The delimitation of Potamarius is currently uncertain given the disjunct distribution of the species in Mesoamerica (Potamarius izabalensis, P. nelsoni and P. usumacintae, from Lake Izabal and Usumacinta River basins in Mexico to Guatemala) and Brazil (P. grandoculis, from coastal lakes in southeastern Brazil). The freshwater Arius labiatus and Hexanematichthys henni from the Peripa and Daule rivers in Ecuador that drain to the Eastern Pacific (EP), have also at times been listed as species inquirenda in Potamarius. Here, we redescribe Arius labiatus, redefine the taxonomic status of Hexanematichthys henni, as junior synonym of Arius labiatus, and describe a new species from Peru that is closely related to Arius labiatus. Based on morphological and molecular phylogenetic evidence, we also describe a new genus (Chinchaysuyoa) for the two South American species.
Keywords: Freshwater species; Molecular; Morphological; Relationships and classification